The Relationship of Accreditation Implementation With the Quality of Health Services in South Konawe District - Harifuddin, Harifuddin; Kamalia, La Ode; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: Health services are an important factor in improving health status. Accreditation data for community health centers in South Konawe Regency show that out of 25 public health centers, there are 6 community health centers (24%) with basic accreditation. This study aims to determine the relationship between the implementation of accreditation and the quality of health services at public health centers in South Konawe Regency in 2022. Methods:This type of research is quantitative, cross sectional study design. The population in this study were 288 health workers who served in 6 community health centers with basic accreditation in South Konawe Regency and a sample of 73 people obtained by Proporsionate Stratified Random Sampling.Result: The results of Fisher's exact test obtained p value (0.022) and phi (0.341) for the implementation of management administration. Then for the implementation of SMEs obtained p value (0.000) and phi (0.588) and the implementation of Individual Health Efforts obtained p value (0.000) and phi (0.572). Conclusion: There is a relationship between the implementation of management administration, the implementation of public health efforts and individual health efforts with the quality of health services at the community health center in South Konawe Regency.